Isolation and Characteristization of Indigenic Diesel Fuel and Gasoline Bacteria from Water Quayside Teluk Bandar Lampung - Fitralia Elyza; Tastaptyani Kurnia Nufutomo (Journal of Multidisciplinary Academic, 2019)
Isolation and Characterization of Solar and Gasoline Indigent Bacteria from the Waters of Teluk Bandar Lampung Pier. Lampung Province is a province surrounded by sea waters. Sea water plays an important role in people's lives, where the sea becomes an important commodity for the production of marine biota that can be consumed by the community, because of the high demand for sea transportation. The expenditure is to remove oil which is dumped into the marine environment, especially in the place where the ship's anchorage is anchored. The methodology in this research is used Poured plate and SPC (Standard Plate Count). Conclusions obtained from the Bacteria coding S2 study have potential bioremediation with the highest S2 cell count of 120 x 105 cells / ml at solar concentrations 3. Bacteria coding S4 has the potential for remediation with a cell number of 130 x 105 cells / ml at 2% gasoline concentration. Petroleum breakers bacteria come from the types of Nitrococcus, Enterobacter, and Achromobacter